ANALISIS PENGELOLAAN SAMPAH DI TRANS DIPO KOTA PEKANBARU - Novera Tanjung Sari; Jufenti Ade Fitri; Riski Novera Yenita; Nofri Hasrianto (Pelantar Press, 2026)
Waste management is a serious challenge in urban areas, including Pekanbaru City, which produces more than 800 tons of waste daily. Trans Dipo, as a Temporary Storage Site (TPS), plays a crucial role in the waste management chain, yet it still faces various technical and community participation challenges. This study aims to determine waste management at Trans Dipo, Pekanbaru City, in 2025, specifically in the aspects of sorting, collection, and transportation. The research method used a qualitative approach with a descriptive design. Primary data was obtained through direct observation and in-depth interviews with supervisors, Trans Dipo officers, and officials from the Pekanbaru City Environment and Sanitation Agency. Secondary data was obtained from official documents from the Ministry of Environment and Forestry. Data analysis was conducted through the stages of reduction, presentation, and drawing conclusions through source triangulation. The results indicate that waste sorting is not optimal because residents still mix organic and inorganic waste, while sorting efforts are carried out only by waste banks. Waste collection is routinely carried out 3–4 times a week, but is still hampered by irregular fees and a lack of community discipline. Transportation from the TPS (landfill) to the TPA (landfill) is carried out daily by dump trucks or Colt Diesel trucks, but fleet limitations and vehicle breakdowns often cause delays, resulting in waste accumulation at the TPS. Overall, waste management at the Trans Dipo in Pekanbaru City is ineffective due to limited infrastructure, low public awareness, and operational constraints. Improvements are needed, including the provision of sorting facilities, additional collection vehicles, and ongoing education to ensure a more optimal and environmentally friendly waste management system